Integrating Network Pharmacology and Experimental Validation to Decipher the Anti-Inflammatory Effects of Magnolol on LPS-induced RAW264.7 Cells - Hao, Lei; Zhong, Xiaoying; Yu, Runjia; Chen, Jiahui; Li, Wei; Chen, Yuzhong; Lu, Weiqi; Wu, Jianyu; Wang, Peizong (Combinatorial Chemistry & High Throughput Screening, 2024)
Introduction: Magnolol is beneficial against inflammation-mediated damage. However, the underlying mechanisms by which magnolol exerts anti-inflammatory effects on macrophages remain unclear. Objective: In this study, network pharmacology and experimental validation were used to assess the effect of magnolol on inflammation caused by lipopolysaccharide (LPS) in RAW264.7 cells. Materials and Methods: Genes related to magnolol were identified in the PubChem and Swiss Target Prediction databases, and gene information about macrophage polarization was retrieved from the GeneCards, OMIM, and PharmGKB databases. Analysis of protein-protein interactions was performed with STRING, and Cytoscape was used to construct a component-target-disease network. GO and KEGG enrichment analyses were performed to ascertain significant molecular biological processes and signaling pathways. LPS was used to construct the inflammatory cell model. ELISA and qRTPCR were used to examine the expression levels of inflammationassociated factors, immunofluorescence was used to examine macrophage markers (CD86 and CD206), and western blotting was used to examine protein expression levels. Results: The hub target genes of magnolol that act on macrophage polarization were MDM2, MMP9, IL-6, TNF, EGFR, AKT1, and ERBB2. The experimental validation results showed that magnolol treatment decreased the levels of proinflammatory factors (TNF-α, IL-1β, and IL-6). Moreover, the levels of anti-inflammatory factors (IL-10 and IL-4) were increased. In addition, magnolol upregulated the expression of M2 markers (Agr-1, Fizzl, and CD206) and downregulated M1 markers (CD86). The cell experiment results supported the network pharmacological results and demonstrated that magnolol alleviated inflammation by modulating the PI3k-Akt and P62/keap1/Nrf2 signaling pathways. Conclusion: According to network pharmacology and experimental validation, magnolol attenuated inflammation in LPS-induced RAW264.7 cells mainly by inhibiting M1 polarization and enhancing M2 polarization by activating the PI3K/Akt and P62/keap1/Nrf2 signaling pathways.
Keywords: Magnolol